The Role of Islamic Microfinance in Strengthening Social Resilience Post-Pandemic - Sahara Sahara (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2025)
This study examines the role of Islamic microfinance in strengthening social resilience among vulnerable communities in the post-pandemic period. Using a mixed qualitative secondary analysis of institutional reports, academic literature, and regulatory documents, the research investigates how Sharia-compliant financing instruments such as qard hasan, profit-sharing schemes, and integrated microenterprise support contribute to income recovery, livelihood stabilization, and community adaptability after COVID-19 disruptions. The findings reveal that Islamic microfinance institutions enhance social resilience by providing accessible capital, flexible repayment structures, and embedded non-financial services, including mentoring, market facilitation, and financial literacy training. These features help micro-entrepreneurs rebuild productive capacity, reduce dependence on high-risk informal lenders, and strengthen household coping mechanisms. The study also identifies governance quality and digital service delivery as key enablers of resilience outcomes. Overall, the results highlight the strategic role of Islamic microfinance as a socio-economic buffer that supports post-crisis recovery and promotes long-term resilience among marginalized groups.